Industry 4.0 - information systems implementation for industrial processes support and optimization - Silva, André Filipe Morais da (2019)
The fourth Industrial revolution is the digital transformation of manufacturing, which incorporates the association of Industrial and Operational Technology, Big Data analysis and organization, coordination between Sensors plus Actuators with Robotics, leading to the Artificial Intelligence. This revolution will also decentralize manufacturing in a smart way, with self-optimization systems and the digital supply chain. One of the fields associated with the new trend of digitization is the Document Management Systems (DMS). The main goal of DMS is to achieve different types of systems which will optimize the operator’s self-decision, increasing productivity and subsequently decreasing cost. One of the biggest problems in all industry is the excess amount of paper produced, which lead to a tremendous decentralized cost. The present work fits in the company's strategy for a more sustainable environment being an initial positive driver of Industry 4.0 implementation. This thesis was supported by the development of two Information Systems (IS), during an internship at Toyota Caetano Portugal, S.A. The systems were developed to reduce waste and increase productivity, through better decision-making. Reducing the action time and provide a faster maintenance were also intended. Two projects were made, one to optimize the material's order and return processes and another for database maintenance and organization. The first project’s main goal was time optimization of the entire materials requirement process from the warehouse, to satisfy the line production needs and reduce paper. Therefore, a DMS was created, providing a better organized way for all process workflow. As a result of this IS implementation, a reduction of 4538 paper sheet consumption per year and time execution process optimization from the stakeholders, 0,10€ and 2,09€ per unit produced respectively, were gained. The maintenance of the logistic database from the Land Cruiser 70 (LC70) produced in the factory was the second project’s main goal. Then a DMS for decision support was developed, which allowed the user to add, edit, duplicate, delete and search every data needed in a faster and more flexible way. The user had also access to the respective image of each selected item for an accurate identification and better decision making. The IS implemented had positive results, by reducing the time decision making, from 65 to 38 minutes, which meant a cost reduction of 1,61€ per unit built, and an efficiency of 42% by providing a faster access to information due to organized structure.